Super-resolution and signal separation in contact Kelvin probe force microscopy of electrochemically active ferroelectric materials - Ziatdinov, Maxim; Kim, Dohyung; Neumayer, Sabine; Collins, Liam; Ahmadi, Mahshid; Vasudevan, Rama K.; Jesse, Stephen; Ann, Myung Hyun; Kim, Jong H.; Kalinin, Sergei V. (Journal of Applied Physics, 2020)
Imaging mechanisms in contact Kelvin probe force microscopy (cKPFM) are explored via information theory-based methods. Gaussian processes are used to achieve super-resolution in the cKPFM signal, effectively extrapolating across the spatial and parameter space. Tensor factorization is applied to reduce the multidimensional signal to the tensor convolution of the scalar functions that show a clear trending behavior with the imaging parameters. These methods establish a workflow for the analysis of the multidimensional datasets that can then be related to the relevant physical mechanisms. We also provide an interactive Google Colab notebook that goes through all the analyses discussed in the paper.
Keywords: Gaussian Processes; Imaging mechanism; Imaging parameters; Kelvin probe force microscopy; Multi-dimensional datasets; Multidimensional signals; Physical mechanism; Tensor factorization